1971
DOI: 10.1007/bf03394023
|View full text |Cite
|
Sign up to set email alerts
|

Research with the Wechsler Intelligence Scales for Adults: 1965–1970

Abstract: 2. FITZHUOH, K. B., FITZHUGH, L. C. and REITAN, R. M. WB comparisons in groups with "chronicJJ and "current" lateralized and diffuse brain lesions. A., WILLCUTT, H. and SMITH, A. Wechsler profiles of mathematically gifted adolescents. Psychol. Rep., 1963, 18, 259-262. 5. KL.+vE, H. and FITZHUOH, K. B. The relationship of differential EEG patterns to the distribution of WB scores in a chronic epileptic population. J . elin. Psychol., 1962, 18, 334-337. 6. KWVE, H. and WHITE, P. T. The relationship of degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

1971
1971
1977
1977

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 186 publications
3
11
0
Order By: Relevance
“…Guertin, et. al., 1962Guertin, et. al., , 1966 thus far has revealed a limited relationship, if any, between I& and anxiety as measured by instruments such as the MAS (Taylor, 1953).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guertin, et. al., 1962Guertin, et. al., , 1966 thus far has revealed a limited relationship, if any, between I& and anxiety as measured by instruments such as the MAS (Taylor, 1953).…”
Section: Discussionmentioning
confidence: 99%
“…At the conclusion of the experimental procedures, subjects in the stress condition were asked how the stressor, ego-threat instructions, affected them. Several reviewers, such as Guertin et al (1966), I'evitt (1967), Sattler & Theye (1967), suggested that the most important result of the study was that those stressed subjects who reported being disturbed by the instructions scored significantly lower on D than did the controls, whereas the nondisturbed stressed subjects performed on a par with controls. Walker and Spence (1964) concluded their report by recommending that investigators interested in the anxiety reactions of their subjects might do well to ask the subjects.…”
mentioning
confidence: 99%
“…Guertin, et a1. (l0, 11) stressed the possible contaminating effects of a failure to consider systematically the relevant variables. Thus, according to Guertin, "Research in the area seems t o be where it was a t the time of our first W-B review 20 years ago(l*).…”
Section: Problemmentioning
confidence: 99%
“…For example, factors such as retardation ( 4 ) and cultural and educational (5) deprivation may provide as tenable an explanation as do personality characteristics for the inferior performance of criminals and delinquents on Wechsler Adult Intelligence Scale (WAIS) verbal scale subtests. Institutionalization and the chronicity of disorders such as brain injury (2) may have an effect on subtest variations.…”
Section: Problemmentioning
confidence: 99%